Problems of Under Age Marriage - Marmiati Mawardi (Balai Penelitian dan Pengembangan Agama Semarang, 2012)
The industrial development in Wonoayu district contributes to economic growth in society. On the other hand, there is a shift of norms because of open information access that affects sexual intercourse among teenagers. This results in an early marriage because the girls have already been pregnant. This research uses a qualitative approach in order to investigate the influential factors, causes, motives and impact of the early marriage, and how society’s view on early marriage in Wonoayu district. The contributing factors of early marriages are sexual intercourse and pre-marital pregnancy. The motives of early marriage are; religiously legal marriage, reducing economic burden of parent, and preserving social reputation of their parents. Meanwhile the impact of legally formal marriage is to avoid sin and to protect the children’s status legally. Economically, the family in general is not ready to get married, and psychologically they are not mature yet, because they still have strong ego and are not independent.